Let the eccentricity of the hyperbola $\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$ be reciprocal to that of the ellipse ${{x}^{2}}+4{{y}^{2}}=4$. If the hyperbola passes through a focus of the ellipse, then
(a) the equation of hyperbola is $\dfrac {{{x}^{2}}}{3}-\dfrac{{{y}^{2}}}{2}=1$
(b) A focus of hyperbola is $\left( 2,0 \right)$
(c) the eccentricity of hyperbola is $\sqrt{\dfrac{5}{3}}$
(d) the equation of hyperbola is ${{x}^{2}}-3{{y}^{2}}=3$
Answer
Verified
483.3k+ views
Hint: We can use formula for eccentricity and focus and hyperbola because in the given question we have a relation between the eccentricity of ellipse and hyperbola. Then we can use the focus of the ellipse to get the final answer.
Complete step-by-step solution:
In given question equation of ellipse is ${{x}^{2}}+4{{y}^{2}}=4$.
On dividing both sides from 4 to write it in standard form.
$\Rightarrow \dfrac{{{x}^{2}}+4{{y}^{2}}}{4}=\dfrac{4}{4}$
$\Rightarrow \dfrac{{{x}^{2}}}{4}+\dfrac{4{{y}^{2}}}{4}=1$
$\Rightarrow \dfrac{{{x}^{2}}}{4}+{{y}^{2}}=1$
On comparing with $\dfrac{{{x}^{2}}}{{{a}^{2}}}+\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$
$\Rightarrow {{a}^{2}}=4,\,{{b}^{2}}=1$ where a is half of the major axis and b is half of the minor axis.
To calculate eccentricity of ellipse we can use ${{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$
We can arrange it as
$\Rightarrow {{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$
$\Rightarrow \dfrac{{{b}^{2}}}{{{a}^{2}}}=1-{{e}^{2}}$
$\Rightarrow {{e}^{2}}=1-\dfrac{{{b}^{2}}}{{{a}^{2}}}$
On substitute ${{a}^{2}}=4,\,{{b}^{2}}=1$
$\Rightarrow {{e}^{2}}=1-\dfrac{1}{4}$
$\Rightarrow {{e}^{2}}=\dfrac{3}{4}$
$\Rightarrow e=\pm \sqrt{\dfrac{3}{4}}$
$\Rightarrow e=\dfrac{\sqrt{3}}{2}\,or\,\dfrac{-\sqrt{3}}{2}$
But eccentricity of the ellipse always lies between 0 to 1.
Hence
$\Rightarrow e=\dfrac{\sqrt{3}}{2}$
As given in question eccentricity of a hyperbola is reciprocal of the eccentricity of the ellipse.
Let the equation of hyperbola is $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$
Hence eccentricity of hyperbola is $e=\dfrac{2}{\sqrt{3}}$
To calculate eccentricity of hyperbola we can use ${{b}_{1}}^{2}={{a}_{1}}^{2}({{e}^{2}}-1)$ where ${{a}_{1}}$ is the transverse axis of hyperbola and ${{b}_{1}}$ is conjungate axis of hyperbola
On substituting $e=\dfrac{2}{\sqrt{3}}$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( {{\left( \dfrac{2}{\sqrt{3}} \right)}^{2}}-1 \right)$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( \dfrac{4}{3}-1 \right)$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( \dfrac{4-3}{3} \right)$
$\Rightarrow {{b}_{1}}^{2}=\dfrac{{{a}_{1}}^{2}}{3}$………………………………………….(i)
Co-ordinate of focus of ellipse is $\left( \pm ae,0 \right)$ if ${{a}^{2}}>{{b}^{2}}$.
From equation of ellipse $a=2,\,e=\dfrac{\sqrt{3}}{2}$
$\Rightarrow ae=2\times \dfrac{\sqrt{3}}{2}$
$\Rightarrow ae=\sqrt{3}$
Hence co-ordinate of focus of ellipse is $\left( \pm \sqrt{3},0 \right)$
As given, equation of hyperbola passes through focus of ellipse. Hence it will satisfy equation of hyperbola $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$
$\Rightarrow \dfrac{{{\left( \sqrt{3} \right)}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{\left( 0 \right)}^{2}}}{{{b}_{1}}^{2}}=1$
$\Rightarrow \dfrac{3}{{{a}_{1}}^{2}}-0=1$
$\Rightarrow \dfrac{3}{{{a}_{1}}^{2}}=1$
$\Rightarrow {{a}_{1}}^{2}=3$
On substituting ${{a}_{1}}^{2}=3$ in equation (i) ${{b}_{1}}^{2}=\dfrac{{{a}_{1}}^{2}}{3}$
$\Rightarrow {{b}_{1}}^{2}=\dfrac{3}{3}$
$\Rightarrow {{b}_{1}}^{2}=1$
Hence equation of hyperbola is by substituting value of ${{a}_{1}}^{2}$ and ${{b}_{1}}^{2}$
$\Rightarrow \dfrac{{{x}^{2}}}{3}-\dfrac{{{y}^{2}}}{1}=1$
We can simplify by taking L.C.M
$\Rightarrow \dfrac{{{x}^{2}}-3{{y}^{2}}}{3}=1$
$\Rightarrow {{x}^{2}}-3{{y}^{2}}=3$
In general focus of hyperbola is $\left( \pm {{a}_{1}}e,0 \right)$ if ${{a}_{1}}^{2}>{{b}_{1}}^{2}$.
For hyperbola $e=\dfrac{2}{\sqrt{3}},{{a}_{1}}=\sqrt{3}$
$\Rightarrow {{a}_{1}}e=\sqrt{3}\times \dfrac{2}{\sqrt{3}}$
$\Rightarrow {{a}_{1}}e=2$
Hence focus of hyperbola is $\left( \pm 2,0 \right)$.
So option b and d is correct.
Note: In general if equation of ellipse is $\dfrac{{{x}^{2}}}{{{a}^{2}}}+\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$ then eccentricity of ellipse can be calculated from relation ${{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$. Co-ordinate of focus of ellipse is $\left( \pm ae,0 \right)$ if ${{a}^{2}}>{{b}^{2}}$.
If equation of hyperbola is $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$ then eccentricity of hyperbola can be calculated from relation ${{b}_{1}}^{2}={{a}_{1}}^{2}({{e}^{2}}-1)$.
In general eccentricity(e) of the conic section defines its shape and it is a non negative real number.
For ellipse,$0 < e < 1$
For hyperbola, $e >1$
In equations of ellipse and hyperbola if any variable is common then it has to be represented separately to avoid any error arising due to common variable used in the equation
Complete step-by-step solution:
In given question equation of ellipse is ${{x}^{2}}+4{{y}^{2}}=4$.
On dividing both sides from 4 to write it in standard form.
$\Rightarrow \dfrac{{{x}^{2}}+4{{y}^{2}}}{4}=\dfrac{4}{4}$
$\Rightarrow \dfrac{{{x}^{2}}}{4}+\dfrac{4{{y}^{2}}}{4}=1$
$\Rightarrow \dfrac{{{x}^{2}}}{4}+{{y}^{2}}=1$
On comparing with $\dfrac{{{x}^{2}}}{{{a}^{2}}}+\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$
$\Rightarrow {{a}^{2}}=4,\,{{b}^{2}}=1$ where a is half of the major axis and b is half of the minor axis.
To calculate eccentricity of ellipse we can use ${{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$
We can arrange it as
$\Rightarrow {{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$
$\Rightarrow \dfrac{{{b}^{2}}}{{{a}^{2}}}=1-{{e}^{2}}$
$\Rightarrow {{e}^{2}}=1-\dfrac{{{b}^{2}}}{{{a}^{2}}}$
On substitute ${{a}^{2}}=4,\,{{b}^{2}}=1$
$\Rightarrow {{e}^{2}}=1-\dfrac{1}{4}$
$\Rightarrow {{e}^{2}}=\dfrac{3}{4}$
$\Rightarrow e=\pm \sqrt{\dfrac{3}{4}}$
$\Rightarrow e=\dfrac{\sqrt{3}}{2}\,or\,\dfrac{-\sqrt{3}}{2}$
But eccentricity of the ellipse always lies between 0 to 1.
Hence
$\Rightarrow e=\dfrac{\sqrt{3}}{2}$
As given in question eccentricity of a hyperbola is reciprocal of the eccentricity of the ellipse.
Let the equation of hyperbola is $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$
Hence eccentricity of hyperbola is $e=\dfrac{2}{\sqrt{3}}$
To calculate eccentricity of hyperbola we can use ${{b}_{1}}^{2}={{a}_{1}}^{2}({{e}^{2}}-1)$ where ${{a}_{1}}$ is the transverse axis of hyperbola and ${{b}_{1}}$ is conjungate axis of hyperbola
On substituting $e=\dfrac{2}{\sqrt{3}}$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( {{\left( \dfrac{2}{\sqrt{3}} \right)}^{2}}-1 \right)$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( \dfrac{4}{3}-1 \right)$
$\Rightarrow {{b}_{1}}^{2}={{a}_{1}}^{2}\left( \dfrac{4-3}{3} \right)$
$\Rightarrow {{b}_{1}}^{2}=\dfrac{{{a}_{1}}^{2}}{3}$………………………………………….(i)
Co-ordinate of focus of ellipse is $\left( \pm ae,0 \right)$ if ${{a}^{2}}>{{b}^{2}}$.
From equation of ellipse $a=2,\,e=\dfrac{\sqrt{3}}{2}$
$\Rightarrow ae=2\times \dfrac{\sqrt{3}}{2}$
$\Rightarrow ae=\sqrt{3}$
Hence co-ordinate of focus of ellipse is $\left( \pm \sqrt{3},0 \right)$
As given, equation of hyperbola passes through focus of ellipse. Hence it will satisfy equation of hyperbola $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$
$\Rightarrow \dfrac{{{\left( \sqrt{3} \right)}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{\left( 0 \right)}^{2}}}{{{b}_{1}}^{2}}=1$
$\Rightarrow \dfrac{3}{{{a}_{1}}^{2}}-0=1$
$\Rightarrow \dfrac{3}{{{a}_{1}}^{2}}=1$
$\Rightarrow {{a}_{1}}^{2}=3$
On substituting ${{a}_{1}}^{2}=3$ in equation (i) ${{b}_{1}}^{2}=\dfrac{{{a}_{1}}^{2}}{3}$
$\Rightarrow {{b}_{1}}^{2}=\dfrac{3}{3}$
$\Rightarrow {{b}_{1}}^{2}=1$
Hence equation of hyperbola is by substituting value of ${{a}_{1}}^{2}$ and ${{b}_{1}}^{2}$
$\Rightarrow \dfrac{{{x}^{2}}}{3}-\dfrac{{{y}^{2}}}{1}=1$
We can simplify by taking L.C.M
$\Rightarrow \dfrac{{{x}^{2}}-3{{y}^{2}}}{3}=1$
$\Rightarrow {{x}^{2}}-3{{y}^{2}}=3$
In general focus of hyperbola is $\left( \pm {{a}_{1}}e,0 \right)$ if ${{a}_{1}}^{2}>{{b}_{1}}^{2}$.
For hyperbola $e=\dfrac{2}{\sqrt{3}},{{a}_{1}}=\sqrt{3}$
$\Rightarrow {{a}_{1}}e=\sqrt{3}\times \dfrac{2}{\sqrt{3}}$
$\Rightarrow {{a}_{1}}e=2$
Hence focus of hyperbola is $\left( \pm 2,0 \right)$.
So option b and d is correct.
Note: In general if equation of ellipse is $\dfrac{{{x}^{2}}}{{{a}^{2}}}+\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$ then eccentricity of ellipse can be calculated from relation ${{b}^{2}}={{a}^{2}}(1-{{e}^{2}})$. Co-ordinate of focus of ellipse is $\left( \pm ae,0 \right)$ if ${{a}^{2}}>{{b}^{2}}$.
If equation of hyperbola is $\dfrac{{{x}^{2}}}{{{a}_{1}}^{2}}-\dfrac{{{y}^{2}}}{{{b}_{1}}^{2}}=1$ then eccentricity of hyperbola can be calculated from relation ${{b}_{1}}^{2}={{a}_{1}}^{2}({{e}^{2}}-1)$.
In general eccentricity(e) of the conic section defines its shape and it is a non negative real number.
For ellipse,$0 < e < 1$
For hyperbola, $e >1$
In equations of ellipse and hyperbola if any variable is common then it has to be represented separately to avoid any error arising due to common variable used in the equation
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE